Preserving Sundanese Pupuh Culture through Flipbook Media: Strengthening Mutual Cooperation in Early Childhood Education - Purnamasari, Yayu Mega; Jazariyah; Windarta, Libri Rizka Puri; Mulqiah, Amanda Rizkiyani (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
The Sundanese Pupuh culture is declining, marked by its limited introduction in schools, especially in early childhood education. Preservation efforts are needed from an early age and can be integrated with the P5 program (Project for Strengthening the Profile of Pancasila Students). This study aims to develop a flipbook media product based on Sundanese Pupuh culture to strengthen P5, particularly in the dimension of mutual cooperation. The media product is a story derived from the adaptation of the Gambuh pupuh, which has been transformed into a flipbook format. The approach used in this development research is the ADDIE model with the steps of analysis, design, development, implementation, and evaluation. The developed product was evaluated for feasibility by media experts and content experts. After being deemed feasible, the product was tested for effectiveness with 8 teachers and 34 students from two schools. Data were collected through expert questionnaires, teacher responses, and observations. The data obtained were analyzed using a descriptive quantitative approach. The feasibility test results showed a 92% rating from content experts and 91% from media experts, both categorized as "very feasible." Teacher response tests yielded 80%, indicating suitability for use. The effectiveness test results showed that 88% of the children were in the "emerged" category, while 12% were not yet emerged. This indicates that the Sundanese Pupuh-based flipbook can strengthen the mutual cooperation dimension in early childhood education. The innovation of flipbooks based on Sundanese poems has implications for strengthening local culture for PAUD students.